Use of Viscoelastography in Malignancy-Associated Coagulopathy and Thrombosis: A Review - Walsh, Mark; Moore, Ernest E.; Moore, Hunter; Thomas, Scott; Lune, Stefani Vande; Zimmer, David; Dynako, Joseph; Hake, Daniel; Crowell, Zachary; McCauley, Ross; Larson, Emilee E.; Miller, Michael; Pohlman, Tim; Achneck, Hardean E.; Martin, Peter; Nielsen, Nathan; Shariff, Faisal; Ploplis, Victoria A.; Castellino, Francis J. (Seminars in Thrombosis and Hemostasis, 2019)
The relationship between malignancy and coagulopathy is one that is well documented yet incompletely understood. Clinicians have attempted to quantify the hypercoagulable state produced in various malignancies using common coagulation tests such as prothrombin time, activated partial thromboplastin time, and platelet count; however, due to these tests' focus on individual aspects of coagulation during one specific time point, they have failed to provide clinicians the complete picture of malignancy-associated coagulopathy (MAC). Viscoelastic tests (VETs), such as thromboelastography (TEG) and rotational thromboelastometry (ROTEM), are whole blood analyses that have the advantage of providing information related to the cumulative effects of plasma clotting factors, platelets, leukocytes, and red cells during all stages of the coagulation and fibrinolytic processes. VETs have gained popularity in the care of trauma patients to objectively measure trauma-induced coagulopathy (TIC), but the utility of VETs remains yet unrealized in many other medical specialties. The authors discuss the similarities and differences between TIC and MAC, and propose a mechanism for the hypercoagulable state of MAC that revolves around the thrombomodulin–thrombin complex as it switches between activating the protein C anticoagulation pathway or the thrombin activatable fibrinolysis inhibitor coagulation pathway. Additionally, they review the current literature on the use of TEG and ROTEM in patients with various malignancies. Although limited research is currently available, early results demonstrate the utility of both TEG and ROTEM in the prediction of hypercoagulable states and thromboembolic complications in oncologic patients.
Keywords: coagulopathy; thromboembolism; ROTEM; TEG; malignancy; tumors; hypercoagulable